Elite outside hitters in volleyball do not meet their individual possible maximum impact height in high spike jumps - Kuhlmann, C.; Roemer, K.; Milani, T. L. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
It is assumed that a high impact height is a relevant factor for success in volleyball spikes. The purpose of the study was to investigate whether outside hitters hit the ball at the highest possible impact height. Spikes from position IV were analysed at a tournament of the European League. The posture of the athletes was less extended in the trunk and upper limb with increasing jump height. Regarding the body posture at the moment of impact, there was no effect on the post impact ball speed. It is concluded that there could be enhancement with respect to the impact height as jump height increases even in elite athletes without reducing ball speed. This should be addressed within the training process.